Undocumented beetle diversity in the Southeastern United States: a case study of the minute clubbed beetles (Coleoptera: Monotomidae) - Mcelrath, Thomas C.; Mchugh, Joseph V. (Zootaxa, 2018)
Studies of the saproxylic and predatory beetle family Monotomidae (Coleoptera: Cucujoidea) in the southeastern USA increased the known diversity for the family in the state of Georgia by one genus and nine species. Online records of Monotomidae from Georgia increased from 0 to 885. This work highlights the lack of basic diversity information about small beetles that inhabit wood, leaf litter, and other decaying plant matter in this region.